2011
DOI: 10.1016/j.jvs.2011.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal insufficiency on clinical outcomes in patients with critical limb ischemia undergoing endovascular revascularization

Abstract: While functional lower limb outcomes were not influenced by renal function in this study, presence of RI was an independent predictor for higher mortality in CLI patients undergoing endovascular revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
(53 reference statements)
2
26
3
1
Order By: Relevance
“…However, data on the relationship between the incidence of SFA restenosis and CKD are limited (13, 17, 18). A retrospective study by Willenberg et al reviewed the impact of renal insufficiency on clinical outcomes among patients treated with endovascular revascularization for CLI (19). In their study, creatinine clearance was a significant predictor for mortality at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the relationship between the incidence of SFA restenosis and CKD are limited (13, 17, 18). A retrospective study by Willenberg et al reviewed the impact of renal insufficiency on clinical outcomes among patients treated with endovascular revascularization for CLI (19). In their study, creatinine clearance was a significant predictor for mortality at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with critical limb ischemia (CLI), arguably the most morbid form of PAD, have a significant burden of AKI risk factors . The rates of diabetes and CKD in unselected studies of the CLI population have been reported to be 30–60% and 10–40%, respectively . Patients with CLI and tissue loss are also exposed to additional nephrotoxic agents such as antibiotic therapy which may also adversely influence renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with claudication undergoing treatment were not included (26). Willenberg et al prospectively followed 208 patients who underwent endovascular treatment and revealed that renal insufficiency was an independent predictor of mortality in CLI patients undergoing endovascular treatment (27). Again, patients with claudication were not included in this study.…”
Section: Discussionmentioning
confidence: 99%